Manuscripts of Václav Kohauth - Bodnárová, Zuzana (Romano džaniben, 2020)
The article describes and analyzes one of the oldest written records of North Central Romani, the Hungarian-Romani glossary Exercitatio Linguae Zingaricae, compiled in 1821 in eastern Slovakia by Canon Václav Kohauth from the monastery in Jasov. The article also includes a transcription of the document with a Czech translation and notes on individual passages.